Briacavatolides A–C, New Briaranes from the Taiwanese Octocoral Briareum excavatum - Yeh, Tsun-Tai (MDPI, 2012)
In order to search for novel bioactive substances from marine organisms, we have investigated the organic extracts of the Taiwanese octocoral Briareum excavatum collected at Orchid Island. Three new briarane-type diterpenoids, briacavatolides A–C (1–3) as well as two known briaranes, briaexcavatolide U (4) and briaexcavatin L (5) were isolated from the acetone extract. The structures of these compounds were elucidated by extensive NMR spectroscopic analysis and physical data. The anti-HCMV (human cytomegalovirus) activity of 1–5 and their cytotoxicity against selected cancer cell lines were evaluated.